Prevalence of Osteopathologies in Children and Adolescents After Diagnosis of Acute Lymphoblastic Leukemia - Schündeln, Michael M.; Hauffa, Pia K.; Munteanu, Martin; Kiewert, Cordula; Unger, Nicole; Bauer, Jens J.; Hauffa, Berthold P.; Grasemann, Corinna (Frontiers in Pediatrics, 2020)
Background: Impaired bone health is a late effect of childhood malignancies which can be difficult to detect in juvenile survivors. It may, however, lead to compromised quality of life, or even permanent disability later in life due to osteoporosis, pain or fractures if left untreated. Acute lymphoblastic leukemia (ALL) is the most frequent childhood malignancy with an over 85% five-year survival. ALL and its treatment cause bone alterations in adults, but little information on the bone health status in juvenile survivors is available. Objective: To report data on skeletal late effects in juvenile survivors of childhood ALL based on a comprehensive assessment of bone health and to assess the influence of a vitamin D deficiency on bone health in this cohort. Methods: In a single center cross sectional study 128 pediatric patients (11.94.76 years) with a mean follow up of 5.883.75 years after diagnosis of ALL were recruited. The bone health status of the survivors was assessed based on clinical examination, review of medical records, biochemical and radiographic analyses, by clinical experts. A score which utilized 8 different parameters was formed and used to assess the effect of a vitamin D deficiency on bone health. Results: In this cohort, 18% of survivors displayed overt osteopathologies as defined by clinical expert assessment. Impaired bone health, defined by at least one pathological screening parameter, was detected in 77%. Despite recommendations for adequate vitamin D supplementation, 15% displayed a vitamin D deficiency associated with hyperparathyroidism. The applied score identified survivors with osteopathologies with high sensitivity and specificity. The median score did not differ between patients without and with severe vitamin D deficiency. Conclusion: Our findings suggest that impaired bone health and osteopathologies are common skeletal late effects following treatment of childhood ALL. Major contributing factors are BMT, irradiation and older age at diagnosis. Vitamin D deficiency likely accounts for hyperparathyroidism in some patients but does not seem to further affect bone health in this cohort. Survivors of ALL need thorough surveillance to investigate bone health, since bone morbidity is common and still poorly understood. Early detection and appropriate intervention may improve bone health.